Про забезпечення надійності об'єктів ракетно-космічної техніки на етапі проєктування - Пошивалов, В.П.; Данієв, Ю.Ф.; Резниченко, Л.В.; Телегіна, І.І. (Технічна механіка, 2020)
DOI: doi.org/10.15407/itm2020.01.067